Weed Management on the Abundance of Insect Natural Enemies in a Cabbage Field - Sri Nur Aminah Ngatimin; Syatrawati Syatrawati; Rosi Widarawati (Hasanuddin University, 2013)
The study was conducted to determine the effect of weed management level on the abundance of insect natural enemies in cabbage fields. Two levels of weed management were applied in the field, namely with and without herbicide application in two growers’ cabbage fields in Malino, South Sulawesi, Indonesia. Results demonstrated that insect natural enemies were more abundant in the field without herbicide application than those in the field with herbicide application. Five species of predatory insect species were collected from both fields, anmely Solenopsis sp., Ophionea sp., Euborellia sp., Cicindella sp., and Paederus fuscipes. The herbicide and its surroundings were kept weed-free during the growing season. Four most abundant weed species were found in the field without herbicide treatment including Nasturtium indicum (Brassicaceae), Galinsoga parviflora (Asteraceae), Ageratum conyzoides (Asteraceae) and Cleome rutidospema (Capparidaceae).